2020
DOI: 10.3233/jad-200598
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 Regulates Membrane Homeostatic Pathways that are Dysregulated in Alzheimer’s Disease

Abstract: Mutations in the PSEN1 gene, encoding presenilin 1 (PS1), are the most common cause of familial Alzheimer’s disease (fAD). Since the first mutations in the PSEN1 gene were discovered more than 25 years ago, many postulated functions of PS1 have been investigated. The majority of earlier studies focused on its role as the catalytic component of the γ-secretase complex, which in concert with β site amyloid precursor protein cleaving enzyme 1 (BACE1), mediates the formation of Aβ from amyloid-β protein precursor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…As such, presenilin 1 and 2 mutants form the main genetic risk factors for familial Alzheimer's disease (FAD). In addition to this function, presenilins perform various γ-secretase-independent roles, such as modulation of intracellular Ca 2+ handling [244][245][246][247][248].…”
Section: Presenilinsmentioning
confidence: 99%
“…As such, presenilin 1 and 2 mutants form the main genetic risk factors for familial Alzheimer's disease (FAD). In addition to this function, presenilins perform various γ-secretase-independent roles, such as modulation of intracellular Ca 2+ handling [244][245][246][247][248].…”
Section: Presenilinsmentioning
confidence: 99%
“…In addition, reduced organelle synthesis in ER that degrades misfolded proteins is also closely associated with the development of neurodegenerative diseases [ 42 , 43 ]. It is reported that ER stress can be induced by mutations in the PSEN1 gene contributing consequently to dysfunctional lysosome synthesis, a cause potentially responsible for familial AD [ 44 ]. Therefore, these findings lend strong support to our notion that FOXO1 plays an essential role in protein processing and maturation and is closely associated with the pathology of proteotoxicity-related diseases such as AD and HD.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in either gene cause early‐onset AD 58 and SNCA accumulation in Lewy bodies (LBs) in these patients 59 . Besides their established role in mediating the formation of Aβ peptide, more recently mutant PS1 has been shown to impair numerous cellular functions, such as calcium flux, organization of proteins in different compartments, and protein turnover via vacuolar metabolism 60 . Interestingly, a novel PSEN1 mutation was recently identified as the likely cause for early‐onset parkinsonism 61 …”
Section: Discussionmentioning
confidence: 99%